A new species of Bibarba (Teleostei: Cypriniformes: Cobitidae) from Guangxi, China - Wu, Tie-Jun; Yang, Jian; Xiu, Li-Hui (Zootaxa, 2015)
A new loach species of the genus Bibarba is described from a cave (Hongshuihe River basin) in Guangxi, China. The new species, Bibarba parvoculus, can be distinguished from its only congener Bibarba bibarba by pigmentation patterns on fins and side of the body, shape of snout, counts of fin rays, eye diameter, caudal-peduncle length, and preanal length.